2013
DOI: 10.1002/hipo.22150
|View full text |Cite
|
Sign up to set email alerts
|

Novel nootropic drug sunifiram enhances hippocampal synaptic efficacy via glycine‐binding site of N‐methyl‐D‐aspartate receptor

Abstract: Sunifiram is a novel pyrrolidone nootropic drug structurally related to piracetam, which was developed for neurodegenerative disorder like Alzheimer's disease. Sunifiram is known to enhance cognitive function in some behavioral experiments such as Morris water maze task. To address question whether sunifiram affects N-methyl-D-aspartate receptor (NMDAR)-dependent synaptic function in the hippocampal CA1 region, we assessed the effects of sunifiram on NMDAR-dependent long-term potentiation (LTP) by electrophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Sunifiram is observed to ameliorate the memory function and has less adverse effects [ 81 ]. A recent study reports the improvement of hippocampal LTP induced by sunifiram is mediated by the glycine-binding site of NMDA receptor [ 101 ], an attractive binding site for Alzheimer's disease drugs [ 102 ]. Thus, the reaction of sunifiram on the same binding site is suggested to ameliorate the impaired cognitive function of Alzheimer's disease patients [ 101 ].…”
Section: Examples Of Nootropicmentioning
confidence: 99%
“…Sunifiram is observed to ameliorate the memory function and has less adverse effects [ 81 ]. A recent study reports the improvement of hippocampal LTP induced by sunifiram is mediated by the glycine-binding site of NMDA receptor [ 101 ], an attractive binding site for Alzheimer's disease drugs [ 102 ]. Thus, the reaction of sunifiram on the same binding site is suggested to ameliorate the impaired cognitive function of Alzheimer's disease patients [ 101 ].…”
Section: Examples Of Nootropicmentioning
confidence: 99%
“…Interestingly, sunifiram‐induced enhancement of hippocampal LTP is mediated by NMDAR‐dependent Src activation and in turn ERK (Moriguchi et al . ). In contrast, rivastigmine failed to stimulate tyrosine phosphorylation GluN2B (Tyr‐1472) and ERK.…”
Section: Discussionmentioning
confidence: 97%
“…We recently introduced nootropic drug sunifiram, which stimulates NMDAR through its activation of glycine biding site, thereby enhancing CaMKII activity and LTP in OBX mouse hippocampus (Moriguchi et al 2013). Interestingly, sunifiram-induced enhancement of hippocampal LTP is mediated by NMDAR-dependent Src activation and in turn ERK (Moriguchi et al 2013). In contrast, rivastigmine failed to stimulate tyrosine phosphorylation GluN2B (Tyr-1472) and ERK.…”
Section: Discussionmentioning
confidence: 99%
“…From these and other experiments, the authors concluded that these data indicate that Sunifiram ameliorates OBX-induced deficits of memory-related behaviors and impaired LTP in the hippocampal CA1 region via stimulation of glycine-binding site of N-methyl-D-aspartate receptor (NMDA-R). In the second paper 29 , the authors, to address the question whether Sunifiram affects (NMDAR)-dependent synaptic function in the hippocampal CA1 region, studied the effects of Sunifiram on NMDAR-dependent LTP confirming that Sunifiram enhances hippocampal synaptic efficacy via glycine-binding site of NMDA receptor. At the moment, the relation of this result with our finding on AMPA receptors involvement is unclear.…”
Section: The Problem Of the Mechanism Of Actionmentioning
confidence: 99%